Information Technology as Science: A New Model for Learning - Puguh Jayadi; Fathul Wahid (IJID (International Journal on Informatics for Development), 2019)
The integration of learning and Information Technology (IT) currently has a good impact on education. Besides making it easy, IT also provides opportunities to achieve learning goals anytime and anywhere. Many studies have discussed how to achieve successful learning through IT. IT here only serves as a support for learning, not as a science. This research develops a model or instrument used to achieve learning success by placing IT as a science. As a result, a learning model was successfully developed by combining several perspectives related to IT; students (Background, desire, and skill), teacher (teaching), and institution (infrastructure).